Pengaruh Rasio Margin Laba, Rasio Lancar, Rasio Cepat,Rasio Utang Jangka Panjang, Rasio Hasil Pengembalian Investasi, Rasio Utang, Rasio Perputaran Piutang, Rasio Hasil Pengembalian Ekuitas Dan Rasio Perputaran Aktiva Tetap Terhadap Pertumbuhan Laba Sebelum Dan Sesudah Pemisahan Air Traffic Control, Studi Kasus Pada PTAngkasa Pura II Persero) Periode 2011 2014 - Umi Khanifah; Erna Listyaningsih; Bambang Purwanto (Jurnal Riset Akuntansi dan Manajemen Malahayati, 2016)
The objective of this research are found regression from net profit margin, current ratio,quick ratio, long term dept to equity ratio, return on inverstment, dept to equity ratio, turn over ratio,return on equity and fixed asset turn over ratio toward growing profit (before and after separation AirTraffic Control, case study in PT Angkasa Pura II Persero) with partial altough simultaneous. Andalso for found the different of financial performance in PT Angkasa Pura II (before and afterseparation Air Traffic Control, case study in PT Angkasa Pura II Persero) with used Paired Sample ttest.The research used approachment quantitative. Data used in this research is secondary data likeas financial quartely report PT Angkasa Pura II (Persero) period 2011 2014. Population from thisresearch is financial report PT Angkasa Pura II (Persero) from years 1984 2014. Taken sampletechnique that used Sistematic Sampling, with period from years 2011 2014. Method for analysisdata is regression linear analysis method and different test Paired Sample t-test that processed usedSPSS 20.0 program for windows. The result have indicate with partial test, only net profit margin thathave significat regression toward growing profit while current ratio, quick ratio, long term dept toequity ratio, return on inverstment, dept to equity ratio, turn over ratio, return on equity and fixedegression toward growing profit in PT Angkasa Pura II(Persero). The result from Simultaneous test have indicate if net profit margin that have significantregression toward growing profit while current ratio, quick ratio, long term dept to equity ratio,return on inverstment, dept to equity ratio, turn over ratio, return on equity and fixed asset turn overPT Angkasa Pura II (Persero). And forresult from different test Paired sample t-test have indicate if perfomance financial before and afterseparation Air Traffic Control is different. Performance Financial before separation Air TrafficControl more better than after separation Air Traffic Control